Expert SQL server 2008 development - Aitchison, Alastair (Expert's voice in SQL server., 2009)
Expert SQL Server 2008 Development is aimed at SQL Server developers ready to move beyond Books Online. Author and experienced developer Alastair Aitchison shows you how to think about SQL Server development as if it were any other type of development. You'll learn to manage testing in SQL Server and to properly deal with errors and exceptions. The book also covers critical, database-centric topics such as managing concurrency and securing your data and code through proper privileges and authorization. Alastair places focus on sound development and architectural practices that will help you be.